2001
DOI: 10.1016/s0378-1097(01)00119-7
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutations in the flagella biosynthetic pathway of the solvent-tolerant Pseudomonas putida S12 result in a decreased expression of solvent efflux genes

Abstract: Fourteen solvent-sensitive transposon mutants were generated from the solvent-tolerant Pseudomonas putida strain S12 by applying the TnMod-KmO mutagenesis system. These mutants were unable to grow in the presence of octanol and toluene. By cloning the region flanking the transposon insertion point a partial sequence of the interrupted genes was determined. Comparison of the deduced amino acid sequences with a protein database revealed the following interrupted putative gene products: organic solvent efflux pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
(47 reference statements)
1
12
1
1
Order By: Relevance
“…Early studies by Ramos et al (21) revealed that P. putida DOT-T1E with innate solvent tolerance also showed traits related to phase variation; i.e., 1 out of 10 4 cells survived a sudden toluene shock. Our group and other groups had previously found that mutations in the flagellar export machinery led to solvent sensitivity in P. putida DOT-T1E (24) and S12 (13). Interestingly, we have now found in P. putida DOT-T1E a phase variation associated with flagellum biosynthesis linked to the flhB gene, which correlates with the innate solvent tolerance of this strain.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Early studies by Ramos et al (21) revealed that P. putida DOT-T1E with innate solvent tolerance also showed traits related to phase variation; i.e., 1 out of 10 4 cells survived a sudden toluene shock. Our group and other groups had previously found that mutations in the flagellar export machinery led to solvent sensitivity in P. putida DOT-T1E (24) and S12 (13). Interestingly, we have now found in P. putida DOT-T1E a phase variation associated with flagellum biosynthesis linked to the flhB gene, which correlates with the innate solvent tolerance of this strain.…”
supporting
confidence: 66%
“…In Pseudomonas putida DOT-T1E and P. putida S12, flagellar genes have been shown to be involved in organic solvent tolerance, although the role of their proteins in solvent tolerance remains unclear (13,24). Organic solvents with a logP ow (logarithm of its partition coefficient in n-octanol and water) between 1.5 and 4.0 are extremely toxic for microorganisms and other living cells because they partition preferentially in the cytoplasmic membrane, disorganizing its structure and impairing vital functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the C-terminal 100 amino acids of the SigF proteins do not have similarities to other proteins or domains, including the region 4 domains (Pfam domain number PF04545) containing the Ϫ35 promoter-binding element. AY-WB SigF proteins showed the greatest similarity (E value, 10 Ϫ6 ) to the stress response sigma factor [sigma(H)] of Streptococcus coelicolor (50) and the flagellar biosynthesis sigma factor FliA of Pseudomonas putida (46). Expression of SigF and other PMU genes might occur under specific environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although extrusion of the solvent by efflux pumps is probably the most important mechanism leading to solvent resistance, some other factors have been identified as being involved in the solvent tolerance phenomenon. Among these factors are membrane rigidification via isomerization of the cis unsaturated fatty acids into the corresponding trans isomers (18,22), flagellar export proteins (24,50), and formation of membrane vesicles filled with toluene (26).…”
mentioning
confidence: 99%